RESPONSIVITAS IMPLEMENTOR DALAM MENANGANI KERUSAKAN JALAN DI KOTA PEKANBARU (Studi Kasus Jalan Di Kecamatan Tampan) - Uci Wulandari; Hasim As'ari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Road damage is a public problem that is troubling people's lives. The negative impact of road damage is traffic jams, to traffic accidents. This is where the response of the implementor, namely the Office of Public Works and Spatial Planning Pekanbaru City, is needed to respond to the problem of road damage in accordance with Law of the Republic of Indonesia Number 22 of 2009. Responsiveness is the level of sensitivity of the implementor in responding to a problem. Tampan District as one of the districts with the most population in Pekanbaru City, thereby supporting the density of driving activity. The purpose of this research is to find out the responsiveness of the Pekanbaru City Public Works and Spatial Planning Agency in Dealing with Road Damage in particular the Tampan District and to determine the obstacles of the Pekanbaru City Public Works and Spatial Planning Office in dealing with road damage. This type of research is qualitative research with a case study approach. Collection of data needed both primary and secondary data is collected through interviews, observations and documentation, then analyzed so that conclusions can be drawn from existing research problems. The results of this study found that the implementor's lack of response to the Public Works and Spatial Planning Office in Pekanbaru in handling road damage, was caused by several inhibiting factors, namely financial factors, human resource factors, facilities and infrastructure factors, and road quantity factors. Keyword: Responsiveness, Implementor, Road Damage